Natural and hybrid immunity following four COVID-19 waves: A prospective cohort study of mothers in South Africa. (November 2022) - Zar, Heather J.; MacGinty, Rae; Workman, Lesley; Botha, Maresa; Johnson, Marina; Hunt, Adam; Burd, Tiffany; Nicol, Mark P.; Flasche, Stefan; Quilty, Billy J.; Goldblatt, David
Summary: Background: More than half the global population has been exposed to SARS-CoV-2. Naturally induced immunity influences the outcome of subsequent exposure to variants and vaccine responses. We measured anti-spike IgG responses to explore the basis for this enhanced immunity. Methods: A prospective cohort study of mothers in a South African community through ancestral/beta/delta/omicron SARS-CoV-2 waves (March 2020-February 2022). Health seeking behaviour/illness were recorded and post-wave serum samples probed for IgG to Spike (CoV2-S-IgG) by ECLISA. To estimate protective CoV2-S-IgG threshold levels, logistic functions were fit to describe the correlation of CoV2-S-IgG measured before a wave and the probability for seroconversion/boosting thereafter for unvaccinated and vaccinated adults. Findings: Despite little disease, 176/339 (51·9%) participants were seropositive following wave 1, rising to 74%, 89·8% and 97·3% after waves 2, 3 and 4 respectively. CoV2-S-IgG induced by natural exposure protected against subsequent SARS-CoV-2 infection with the greatest protection for beta and least for omicron. Vaccination induced higher CoV2-S-IgG in seropositive compared to naïve vaccinees. Amongst seropositive participants, proportions above the 50% protection against infection threshold were 69% (95% CrI: 62, 72) following 1 vaccine dose, 63% (95% CrI: 63, 75) following 2 doses and only 11% (95% CrI: 7, 14) in unvaccinated during the omicron wave. Interpretation: Naturally induced CoV2-S-IgG do not achieve high enough levels to prevent omicron infection in most exposed individuals but are substantially boosted by vaccination leading to significant protection. A single vaccination in those with prior immunity is more immunogenic than 2 doses in a naïve vaccinee and may provide adequate protection. Funding: UK NIH GECO award (GEC111), Wellcome Trust Centre for Infectious Disease Research in Africa (CIDRI), Bill & Melinda Gates Foundation, USA (OPP1017641, OPP1017579) and NIH H3 Africa (U54HG009824, U01AI110466]. HZ is supported by the SA-MRC. MPN is supported by an Australian National Health and Medical Research Council Investigator Grant (APP1174455). BJQ is supported by a grant from the Bill and Melinda Gates Foundation (OPP1139859). Stefan Flasche is supported by a Sir Henry Dale Fellowship jointly funded by the Wellcome Trust and the Royal Society (Grant number 208812/Z/17/Z).